Serum miRNA expression profiles change in autoimmune vitiligo in mice. Issue 2 (February 2014) - Shi, Yu‐Ling; Weiland, Matthew; Lim, Henry W.; Mi, Qing‐Sheng; Zhou, Li
Abstract It is widely believed that non‐segmental vitiligo results from the autoimmune destruction of melanocytes. MicroRNAs (miRNAs), a class of small non‐coding RNAs that negatively regulate gene expression, are involved in the immune cell development and function and regulate the development of autoimmune diseases. Recent studies demonstrate that functional miRNAs can be detected in the serum and serve as biomarkers of various diseases. In the present study, we used a mouse autoimmune vitiligo model, in which melanocyte autoreactive CD4+ T cells were adoptively transferred into Rag1−/− host mice. Serum miRNA expression was profiled in vitiligo developed mice and control mice using TaqMan RT‐PCR arrays. We have found that the expressions of 20 serum miRNAs were changed in vitiligo mice compared to control mice. Three increased miRNAs, miR‐146a, miR‐191, and miR‐342‐3p, were further confirmed by a single TaqMan RT‐PCR. Our findings suggest that miRNAs may be involved in vitiligo development and serum miRNAs could serve as serum biomarkers for vitiligo in mice.